Struggling to Make the Grade : A Review of the Causes and Consequences of the Weak Outcomes of South Africa's Education System - Mlachila, Montfort (IMF Working Papers; Working Paper ;, 2019)
While South Africa has made significant improvements in basic and tertiary education enrollment, the country still suffers from significant challenges in the quality of educational achievement by almost any international metric. The paper finds that money is clearly not the main issue since the South Africa's education budget is comparable to OECD countries as a percent of GDP and exceeds that of most peer sub-Saharan African countries in per capita terms. The main explanatory factors are complex and multifaceted, and are associated with insufficient subject knowledge of some teachers, history, race, language, geographic location, and socio-economic status. Low educational achievement contributes to low productivity growth, and high levels of poverty, unemployment, and inequality. Drawing on the literature, the paper sketches some policy considerations to guide the debate on what works and what does not.